Frequency domain selective tap adaptive algorithms for sparse system identification - Khong,AWH; Lin,X; Doroslovacki,M; Naylor,PA (2008)
We propose a new low complexity and fast converging frequency-domain adaptive algorithm for sparse system identification. This is achieved by exploiting the MMax and SP tap-selection criteria for complexity reduction and fast convergence respectively.....